Shesasayi Vishnu - Temples of India Project Team (Jio Institute, 2024)
Despite the overall Shaiva mood of the Harsha Temple complex, there were once multiple Vaishnav temples on the hill. This particular image of Shesasayi Vishnu or the reclining Vishnu on the serpent Lord Shesa, was likely once the main cultic image inside a now-lost Vaishnav shrine. Nine planets adorn the top of the image, while Vishnu is served by Lakshmi near his feet. Three ayudhapurusa (personification of his weapons) are placed behind him. The reclining Vishnu is shown in his standard iconography wearing a kirita-mukuta, vanamala and with four arms holding a chakra in his left hand above, mace in his right hand which is also supporting his head, flower in his lower right hand while the left lower hand is broken.